2009
DOI: 10.1111/j.1365-2486.2009.01923.x
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐year decrease in plant species richness on a neotropical inselberg: detrimental effects of global warming?

Abstract: International audienceThe census of vascular plants across a 10-year interval (1995-2005) at the fringe of a neotropical rainforest (Nouragues inselberg, French Guiana, South America) revealed that species richness decreased, both at quadrat scale (2 m2) and at the scale of the inselberg (three transects, embracing the whole variation in community composition). Juvenile stages of all tree and shrub species were most severely affected, without any discrimination between life and growth forms, fruit and dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 87 publications
0
27
0
3
Order By: Relevance
“…It may even be thought that present-day climate warming, and accompanying increased frequency of severe El Niño events in the Southern Oscillation Zone (Malhi and Wright, 2004) cause a reversion of the successional progress. Results of a parallel study showed that the recruitment of juveniles of woody species between 1995 and 2005 was severely affected by the severe El-Niño event which occurred in 1997 (Fonty et al, 2009). In this study we observed a decrease of 24% for individuals and 22% for species over the 205 quadrats of the three transects (totalling 410 m 2 ).…”
Section: Stability Of Plant Assemblagesmentioning
confidence: 53%
See 2 more Smart Citations
“…It may even be thought that present-day climate warming, and accompanying increased frequency of severe El Niño events in the Southern Oscillation Zone (Malhi and Wright, 2004) cause a reversion of the successional progress. Results of a parallel study showed that the recruitment of juveniles of woody species between 1995 and 2005 was severely affected by the severe El-Niño event which occurred in 1997 (Fonty et al, 2009). In this study we observed a decrease of 24% for individuals and 22% for species over the 205 quadrats of the three transects (totalling 410 m 2 ).…”
Section: Stability Of Plant Assemblagesmentioning
confidence: 53%
“…In a previous paper, we reported a marked decrease in plant species richness and tree recruitment in a 10-yr period (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) embracing a severe El-Niño event in 1997 (Fonty et al, 2009). In the present study, we explored the community scale and questioned the temporal change of the vegetation on the ecotone gradient over the same period.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the understorey of the tall-tree rain forest, the air temperature varies from 24.9°C to 28.5°C and the air humidity varies from 84.4% to 96.7% (FF, personal data, 2008). More detailed climate data, including present-day warming trends, are available in Fonty et al (2009). Soils are acid (pH < 5) claysandy Ferralsols (FAO 2006) with a micro-aggregate texture of biological origin and a sparsely distributed litter cover (Grimaldi & Riéra 2001).…”
Section: Study Sitementioning
confidence: 99%
“…We need replicates on a larger scale and to investigate other natural habitat types such as riverine lowland cloud forest (obregon et al 2011), bamboo forest or palm swamp to understand the effects of natural forest dynamics and by extension of anthropogenic disturbance on species distribution. A regular increase in temperature observed over the last 50 years in French Guiana was the most probable cause of plant species richness 10-year decrease in low forest in Nouragues (Fonty et al 2009). Similar trends are predicted in several region of South America (Boulanger et al 2006) which may play direct or indirect role on dung beetle communities through changes in forest structure.…”
Section: Species Compositionmentioning
confidence: 99%